Nonagricultural reservoirs contribute to emergence and evolution of Pseudomonas syringae crop pathogens. Issue 3 (21st May 2013) - Monteil, Caroline L.; Cai, Rongman; Liu, Haijie; Mechan Llontop, Marco E.; Leman, Scotland; Studholme, David J.; Morris, Cindy E.; Vinatzer, Boris A.
Summary: While the existence of environmental reservoirs of human pathogens is well established, less is known about the role of nonagricultural environments in emergence, evolution, and spread of crop pathogens. Here, we analyzed phylogeny, virulence genes, host range, and aggressiveness of Pseudomonas syringae strains closely related to the tomato pathogen P. syringae pv. tomato ( Pto ), including strains isolated from snowpack and streams. The population of Pto relatives in nonagricultural environments was estimated to be large and its diversity to be higher than that of the population of Pto and its relatives on crops. Ancestors of environmental strains, Pto, and other genetically monomorphic crop pathogens were inferred to have frequently recombined, suggesting an epidemic population structure for P. syringae . Some environmental strains have repertoires of type III‐secreted effectors very similar to Pto, are almost as aggressive on tomato as Pto, but have a wider host range than typical Pto strains. We conclude that crop pathogens may have evolved through a small number of evolutionary events from a population of less aggressive ancestors with a wider host range present in nonagricultural environments. Abstract : See also the Commentary by Goss et al.